Potential therapeutic strategies for quercetin targeting critical pathological mechanisms associated with colon adenocarcinoma and COVID-19 - Li, Xiushen; Liang, Weizheng; Yu, Chengwei; Meng, Qingxue; Zhang, Weiwen; Wu, Xueliang; Xue, Jun; Deng, Shoulong; Wang, Hao (Frontiers in Pharmacology, 2022)
Colon adenocarcinoma (COAD) patients are at a higher probability of infection with COVID-19 compared to healthy individuals. However, there is no globally accepted treatment option for patients with COAD/COVID-19. Quercetin has been found to have significant antitumor, antiviral and anti-inflammatory effects in several studies. This study therefore sought to evaluate the potential of quercetin as the agent for COAD/COVID-19 and to explore its mechanisms. We used transcriptome sequencing data from patients to obtain COAD/COVID-19 related genes (CCRGs), and used these genes to construct a COAD prognostic model. We intersected the CCRGs with the therapeutic target genes of quercetin and obtained a total of 105 genes (potential target genes of quercetin for COAD/COVID-19). By constructing a protein-protein interaction (PPI) network, we ascertained FOS, NFKB1, NFKB1A, JUNB, and JUN as possible core target genes for quercetin treatment in patients with COAD/COVID-19 comorbidity. Bioinformatic analysis of these 105 targets revealed that the mechanisms of quercetin treatment in COAD/COVID-19 may be associated with oxidative stress, apoptosis, anti-inflammatory, immune, anti-viral and multiple pathways containing IL-17, TNF, HIF-1. This study is the first to elucidate the target genes and molecular mechanisms of quercetin for COAD/COVID-19, which may be useful for the clinical management of COAD/COVID-19 patients. However, the results have not yet been subjected to molecular biology studies and further clinical trials, so further validation is needed, and this aspect will be the direction of our future research.